DINIYAH PROGRAM ADVANCEMENT: ENHANCING STUDENT LEARNING QUALITY THROUGH COMPREHENSIVE DEVELOPMENT - Niken Septantiningtyas; Sulistiawati, Sulistiawati (Managere: Indonesian Journal of Educational Management, 2023)
This research examines the impact of developing the Diniyah Program as an innovative strategy for improving the quality of student learning in Madrasah. The Diniyah program is integrated as an essential component in the madrasah curriculum with the hope of making a significant contribution to the holistic development of learners. Through an in-depth analysis of the implementation of the Diniyah Program, this study aims to investigate the role of the program in improving the quality of learning, involving religious aspects, critical thinking skills, curriculum integration, moral character building, and promotion of diversity tolerance. The research methodology involves a qualitative approach with data collection through interviews, classroom observation, and analysis of curriculum-related documents. The results showed that (1) the development of the Diniyah Program has had a significant positive impact in improving the quality of student learning. (2) Learners demonstrate progress in religious understanding, development of critical thinking skills, and balanced integration between religious aspects and general science. In addition, (3) the Diniyah Program also has a role in shaping students' moral character, creating individuals who have integrity and good ethics. Tolerance and diversity have also increased, creating an inclusive madrasah environment.